Brain Responses to Movie Trailers Predict Individual Preferences for Movies and Their Population-Wide Commercial Success. (August 2015) - Boksem, Maarten A.S.; Smidts, Ale
Although much progress has been made in relating brain activations to choice behavior, evidence that neural measures could actually be useful for predicting the success of marketing actions remains limited. To be of added value, neural measures should significantly increase predictive power, beyond conventional measures. In the present study, the authors obtain both stated preference measures and neural measures (electroencephalography; EEG) in response to advertisements for commercially released movies (i.e., movie trailers) to probe their potential to provide insight into participants' individual preferences as well as movie sales in the general population. The results show that EEG measures (beta and gamma oscillations), beyond stated preference measures, provide unique information regarding individual and population-wide preference and can thus, in principle, be used as a neural marker for commercial success. As such, these results provide the first evidence that EEG measures are related to real-world outcomes and that these neural measures can significantly add to models predicting choice behavior relative to models that include only stated preference measures.